Towards a restructuring of the conferences? Proposals for their viability - López-Borrull, Alexandre (Anuario ThinkEPI, 2012)
Academic and scientific conferences must cope in the coming years with a restructuring of their delivery formats and contents if they are to survive. The evolution towards the social web 2.0 has to be considered at the same time. A range of solutions are offered, including the link with special issues with consolidated academic journals. The main prospect is the creation of a classification of conferences that can increase their value in the context of evaluating the curriculum vitae of scientific researchers.
Keywords: Academic conferences; Scientific journals; Classification; Evaluation.